Implementation of differentiated learning with problem-based learning model assisted by ‘Mebel InterTika’ - Retno Yuniarti; Nur Izzati; Roma Doni Azmi (Fakultas Tarbiyah Universitas Ibrahimy, 2024)
Problems that often arise in mathematics subjects include low learning outcomes.. This study aims to analyze the differences in learning outcomes of students who learn by implementing differentiated learning strategies with the Problem-Based Learning model assisted by MeBel InterTika with students who learn by implementing the Problem-Based Learning model in class VIII statistics material. This research uses a quantitative approach with a quasi-experimental research type. Data were collected using questionnaire techniques, test techniques, and observation techniques. The main research instruments include a learning style questionnaire, learning results tests, and observation sheets. Supporting research instruments are Learning Implementation Plans and MeBel InterTika. The data analyzed are quantitative data obtained from pretest and posttest data on student learning outcomes in the experimental and control classes. The results of the nonparametric test using the Mann-Whitney test, with a significance level of 5%, obtained a significance value of 0.0175, so it was found that the increase in student learning outcomes through the application of differentiated learning strategies with the Problem-Based Learning model assisted by MeBel InterTika was significantly higher than students who received the Problem-Based Learning model in grade VIII of Junior High School.